Blue Carbon Stocks and Cross-Habitat Subsidies - Bulmer, Richard Hugh; Stephenson, Fabrice; Jones, Hannah F. E.; Townsend, Michael; Hillman, Jenny R.; Schwendenmann, Luitgard; Lundquist, Carolyn J. (Frontiers in Marine Science, 2020)
Blue carbon ecosystems (including saltmarsh, mangrove, seagrass meadows, and other soft sediment habitats) play a valuable role in aquatic carbon dynamics and contribute significantly to global climate change mitigation. However, these habitats are undergoing rapid and accelerating shifts in extent due to climate change and anthropogenic impactsstressors. Here, we demonstrate that blue carbon stocks vary across habitats and that cross-habitat subsidies of carbon contribute significantly to blue carbon stocks. Using a case study estuary from New Zealand, organic carbon stocks in above ground biomass and sediment to 100 cm varied significantly between habitat types, from saltmarsh (90 t ha-1), to mangrove (46 t ha-1), to seagrass (27 t ha-1) and unvegetated habitats (26 t ha-1). Despite being typically overlooked in blue carbon literature, unvegetated habitats contained the majority of estuarine carbon stocks when adjusted for their large extent within the estuary (occupying 68.4% of the estuarine area and containing 57% of carbon stocks). When carbon stocks were further refined based on δ13C and δ15N mixing model results, coastal vegetation (saltmarsh, mangrove, seagrass) was found to provide important cross-habitat subsidies exchanges of carbon throughout the estuary, including contributing an estimated 41% of organic carbon within unvegetated sediments, and 51% of the total carbon stock throughout the estuary (yet occupying only 31.6% of the estuary). Given the connected nature of blue carbon ecosystems these findings illustrate the importance of considering the contribution and cross habitat subsidies of both vegetated and unvegetated habitats to blue carbon stocks in estuaries. This provides critical context when assessing the impact of shifts in habitat distributions due to impacts from climate change and anthropogenic stressors.